Diversity of Epiphytic Orchids, Hoya, Dischidia and Phorophytes (Host Trees) in Bawean Island Nature Reserve and Wildlife Reserve, East Java, Indonesia - Trimanto Trimanto; Setyawan Agung Danarto (Journal of Tropical Biodiversity and Biotechnology, 2020)
Bawean Island is a small island located between two islands (Java and Borneo). Geographically, the diversity of plants, especially epiphytic plants on this island is very interesting to be studied. This research aims to investigate the diversity of epiphytic plants, focussing on epiphytic orchids, Hoya and Dischidia in Bawean Island Nature Reserve and Wildlife Reserve. It was conducted through an inventory of epiphytic orchids and hoya growing on host trees. The results showed there were 10 species of epiphytic orchid and 3 species of epiphytic Hoya, and 1 species of Dischidia growing on-location studies. The epiphytic orchids which found in location studies included Phalaenopsis amabilis, Aerides odorata, Cymbidium aloifolium, Dendrobium anosmum, Rhynchostylis retusa, Liparis condylobulbon, Taeniophyllum biocellatum, Cymbidium sp., Eria sp. Orchid species that most often found in the study location was Phalaenopsis amabilis. In addition, this study recorded Taeniophyllum biocellatum as an endemic orchid from Java that was found on this island. The epiphytic Hoya recorded in there, i.e. Hoya diversifolia, H. verticillata, and H. amoena, and also only found 1 species of  Dischidia was Dischidia imbricata. There were 12 species of trees as the host trees of epiphytic, i.e. Irvingia malayana, Tectona grandis, Diospyros buxyfolius were the host trees frequently found as the host of the epiphytic plant. Zone 3 as an area of 1/3 basal part of a total length of the branches was the most preferred zone by epiphytic orchids and hoya. The epiphytic orchid and hoya hardly found in Zone 5.